T Cell Receptor (TCR)-Induced PLC-γ1 Sumoylation via PIASxβ and PIAS3 SUMO E3 Ligases Regulates the Microcluster Assembly and Physiological Function of PLC-γ1 - Wang, Qi-Long; Liang, Jia-Qi; Gong, Bei-Ni; Xie, Ji-Ji; Yi, Yu-Ting; Lan, Xin; Li, Yingqiu (Frontiers in Immunology, 2019)
The SUMO modification system plays an important role in T cell activation, yet how sumoylation regulates TCR-proximal signalling remains largely unknown. We show here that Phospholipase C-γ1 (PLC-γ1) is conjugated by SUMO1 at K54 and K987 upon TCR stimulation and that K54 sumoylation is pivotal for PLC-γ1-mediated T cell activation. We further demonstrate that TCR-induced K54 sumoylation of PLC-γ1 significantly promotes the formation of PLC-γ1 microclusters and the association of PLC-γ1 with the adaptor proteins SLP76 and Gads，but only slightly affects the phosphorylation of PLC-γ1 on Y783, which determines the enzyme catalytic activity. Moreover, upon TCR stimulation, the SUMO E3 ligases PIASxβ and PIAS3 both interact with PLC-γ1 and cooperate to sumoylate PLC-γ1, facilitating the assembly of PLC-γ1 microclusters. Together, our findings reveal a critical role of PLC-γ1 K54 sumoylation in PLC-γ1 microcluster assembly that controls PLC-γ1-mediated T cell activation, suggesting that sumoylation may have an important role in the microcluster assembly of TCR-proximal signalling proteins.